The best interests of the child in same-sex couples’ procedures for obtaining children - Lyakh, Karina (Bioethica, 2025)
The International Convention on the Rights of the Child mandates that the best interests of the child should be the primary consideration in all decisions affecting them. A key principle of the Convention is non-discrimination, ensuring that children are not discriminated against based on their parents' sexual orientation. States must ensure that children of same-sex families receive equal treatment to those of heterosexual families by enacting legislation that protects their rights. Recognizing and safeguarding the rights of these children contributes to creating a society free from discrimination and prejudice. Regarding the rights of embryos, laws vary by country concerning the recognition of their personhood. Embryo protection should not override women's rights. The embryo is indirectly protected through the mother and is not considered a full person. The viability criterion is significant as it determines the embryo's ability to live independently without granting it full legal protection as a person.